INNOVATIVE LEARNING THROUGH AI: NURTURING CREATIVITY IN THE CLASSROOM - Maftuna Ruzieva (Modern American Journals, 2025)
This study investigates the impact of generative artificial intelligence (AI) on student creativity in higher education, focusing on its pedagogical integration within English language instruction. Conducted at two universities in Uzbekistan with 120 undergraduate participants, the research employed a quasi-experimental mixed-methods design, incorporating pre- and post-tests using the Torrance Tests of Creative Thinking (TTCT), perception surveys, and qualitative observation. Students in the experimental group used AI tool - ChatGPT to complete creative academic tasks, while the control group followed conventional methods. Results revealed a 15.2% improvement in TTCT scores among AI-supported learners, along with enhanced self-perceptions of creativity and task preparedness. Qualitative data further highlighted increased engagement, ideation fluency, and creative complexity in the AI-assisted group. While the study confirms that generative AI can serve as a catalyst for creative thinking, it also emphasizes the necessity of guided implementation to avoid overreliance and preserve learner agency. The findings advocate for pedagogically grounded AI integration to foster meaningful and ethical creativity in modern classrooms.
Keywords: Generative Artificial Intelligence, Student Creativity, ChatGPT, Torrance Test of Creative Thinking (TTCT), English Language Education, Pedagogical Innovation, Higher Education, AI in Education, Cognitive Development.